The Reality of Mission and “Missionariness” in the SVD Parishes in Agusan del Sur, Philippines - Heriyanto, I Wayan (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2023)
This research study explores the question of becoming a missionary parish in the context of the Society of the Divine Word (SVD) parishes in Agusan del Sur. Specifically, the research deals with the reality of a missionary parish. The “reality” presents the SVD parishes in Agusan del Sur (ADS), Philippines as the locus of mission. It first describes the people of Agusan province along with their culture, religious beliefs, practices, and history. Then it provides a profile of the six parishes and one quasi-parish. This reality is evaluated by exploring the “missionariness” or missionary character of the SVD parishes in Agusan del Sur. This is done in the light of the notion of a missionary parish and in the context of their growth and development.